Synthesis of Fe2o3 nanoparticles from limonite stone the Republic of Yemen: Dr. Nabil Abdullah Noman Alkadas - مجلة الأندلس للعلوم التطبيقية, Dr. Nabil Abdullah Noman Alkadas (مجلة الأندلس للعلوم التطبيقية, 2023)
الملخص EN Fe2O3 nanoparticles have been successfully synthesized and the modification of the preparation method of Fe2O3 nano-particles, is reported here which consists of two stages, beginning with the destruction and separation of iron ore from ironstone. Then, the Fe2O3 nano-particles are synthesized using the coprecipitation method with iron oxide (Fe2O3). It began with the destruction of ironstone and the separation of iron ore from purity stone. Fe2O3 nanoparticles were synthesized by using the coprecipitation method. The characterization of Fe2O3 nanoparticle was done by SEM ,TEM ,XRD and U.V